Improving Lone Work Practice Within a Mental Health Trust: A Quality Improvement Project - Tooba Khan; Khunsha Cheema; Yuyu Htwe; Hannah Liu; Anum Asim (BJPsych Open, 2025)
Aims: Ensuring resident doctors’ safety during lone working is crucial, due to unique risks and challenges faced when working alone. Birmingham and Solihull Mental Health Foundation Trust’s (BSMHFT) current lone working policy recommends local procedures based on risk assessment and site needs. However, gaps in implementation have raised concerns about the consistency and effectiveness of safety measures.